From idea to implementation: the development of biobanking in Russia. The Cardiovascular Therapy and Prevention journal’s top contributing institutions: National Association of Biobanks and Biobanking Specialists (NASBIO) - A. N. Meshkov; M. S. Pokrovskaya; A. S. Glotov; A. I. Ershova; Yu. V. Rodionova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
.